Response of Fission Yeast to Toxic Cations Involves Cooperative Action of the Stress-Activated Protein Kinase Spc1/Sty1 and the Hal4 Protein Kinase - Wang, Ling-yu (American Society for Microbiology, 2005)
Stress-activated protein kinases (SAPKs), members of a mitogen-activated protein kinase (MAPK) subfamily, are highly conserved among eukaryotes. Studies of yeasts demonstrated that SAPKs play pivotal roles in survival responses to high osmolarity, oxidative stress, and heat shock. Here we report a novel physiological role of the fission yeast Spc1 SAPK in cellular resistance to certain cations, such as Na(+), Li(+), and Ca(2+). Strains lacking Spc1 or its activator, Wis1 MAPK kinase, are hypersensitive to these cations. Spc1 positively regulates expression of sod2(+) encoding a Na(+)/H(+) antiporter through Atf1 and other transcription factors. In addition, we have identified a novel Spc1-interacting protein, Hal4, which is highly homologous to the budding yeast Sat4/Hal4 protein kinase. Like its budding yeast counterpart, the fission yeast Hal4 kinase is essential for cellular resistance to Na(+), Li(+), and Ca(2+). The hal4-null phenotype is complemented by overexpression of the Trk1 potassium transporter or increased K(+) in the growth medium, suggesting that Hal4 promotes K(+) uptake, which consequently increases cellular resistance to other cations. Interestingly, the Spc1-Hal4 interaction appears to be required for cellular resistance to Ca(2+) but not Na(+) and Li(+). We propose that Spc1 SAPK and Hal4 kinase cooperatively function to protect cells from the toxic cations.